Using the Total Physical Response Method to Improve Young Learners' Perceptions of Vocabulary Mastery - Jazila, Iklimatul Nur; Megawati, Fika (Indonesian Journal Publisher, 2024)
This study aims to explain how early childhood English language learners are taught English using the Total Physical Response (TPR) technique. This kind of study is qualitative descriptive in nature. The researcher in this study outlines the TPR method-based tasks that instructors and students completed. Teachers and students at kindegarten are the source of the data. There are ten pupils in the class, and their ages range from five to six. Through observation of learning activities, data was gathered. Comprehension and understanding were the criteria examined, and the methods utilized were interviews and observation. Researchers' findings demonstrate that young learners like participating actively in English language learning activities and that students may expand their vocabulary when utilizing the TPR approach. The goal of the project is to help improve English language learning and teaching activities, particularly for younger pupils. The findings of the TPR technique observations made in the classroom and the interviews that researchers did with instructors and students attest to this reality.